Compulsory education laws or incentives from CCT programs?: explaining the rise in secondary school attendance rate in Argentina - Edo, María (2016)
The last decade shows a sizeable increase in school attendance rates for children aged 15 through 17 in Argentina. This could be related to the 2006 National Education Law that made upper-secondary education compulsory. In this paper, instead, we claim that the Asignación Universal por Hijo may be mostly responsible for this improvement. Using a difference-in-difference strategy we estimate that the program accounts for a 3.9 percentage point increase in the probability of attending secondary school among eligible children aged 15 through 17.